Essays in money and banking in honour of R. S. Sayers - Sayers, R. S.; Whittlesey, Charles R.; Wilson, John Stuart Gladstone (Oxford : Clarendon P., 1968)
It is a pleasure to welcome the publication of this volume of essays not only for the intrinsic interest of the wide variety of topics covered but also because it was conceived and brought to fruition by the editors through the desire to pay tribute, on the occasion of his retirement, to the recognized doyen of British scholars working in the field of money and banking. There are thirteen essays in this volume which are an accurate reflection of the breadth of his interest.
Includes bibliographical references and index.
rpm 09/04/2018
Loans
Keywords: Money; Monetary policy; Banks and banking; International finance